Mobile Appointment System For Universities - Alshar'e, Marwan Ibrahim Ahmad (2008)
This study explores the implementation of mobile based application as a mediator at the educational operations. The usage of the mobile devices becomes more popular recently, and the wireless technology producers provide the markets and customers with various kinds of hardware and applications which allow customers to use these services from any where and at any time, and this is the main interest in using the mobile based applications. This study focuses on managing the lecturer consulting hours in order to improve the communication between lecturers and students, which are related to the appointment operations The study aims to take advantages of the wide usage of the mobile application to solve inefficiency in student-lecturer appointments which exists in University Utara Malaysia (UUM), and to shift the existing appointment management operation from desktop based application to mobile-based application.